Plutarch's Cosmological Ethics - Demulder, Bram (Plutarchea Hypomnemata, 2022)
Plutarch of Chaeronea (c. 45-120 CE) is the most prolific and influential moral philosopher in the Platonic tradition. This book is a fundamental reappraisal of Plutarch's ethical thought. It shows how Plutarch based his ethics on his particular interpretation of Plato's cosmology. Our quest for the good life should start by considering the good cosmos in which we live. The practical consequences of this cosmological foundation permeate various domains of Greco-Roman life: the musician, the organiser of a drinking party, and the politician should all be guided by cosmology. After exploring these domains, this book offers in-depth interpretations of two works that can only be fully understood by paying attention to cosmological aspects: Dialogue on Love and On Tranquillity of Mind.